2004
DOI: 10.3136/fstr.10.273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mannooligosaccharides from Coffee on Microbiota and Short Chain Fatty Acids in Rat Cecum

Abstract: The effect of mannooligosaccharides (MOS) obtained from coffee mannan on cecal microbiota and short chain fatty acid production was examined in male Sprague-Dawley rats. The rats were given water and a dietary treatment containing 5 % MOS ad libitum for 28 days. The body weight of those fed the MOS diet showed no significant difference compared with rats that consumed the control diet. The consumption of MOS increased the concentration of bifidobacteria (p < 0.05) and the ratio of bifidobacteria to total micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…(1995) also reported that over 95c~70 of SCFA produced in the large intestine were absorbed into the large intestinal epithelium cell. It was confirmed earlier that SCFA were signih~cantly increased in the cecum of rats fed diets containing MOS (Asano et a/., 2003). Accordingly, the absence of difference in fecal pH in the present experiment is also likely due to the rapid absorption of SCFA produced by MOS from the large intestlne.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…(1995) also reported that over 95c~70 of SCFA produced in the large intestine were absorbed into the large intestinal epithelium cell. It was confirmed earlier that SCFA were signih~cantly increased in the cecum of rats fed diets containing MOS (Asano et a/., 2003). Accordingly, the absence of difference in fecal pH in the present experiment is also likely due to the rapid absorption of SCFA produced by MOS from the large intestlne.…”
Section: Discussionsupporting
confidence: 77%
“…Preparcltion ofc'~ff~e mi.v d/'ink The source of MOS was prepared by thermal hydrolysis of spent coffee grounds according to the procedure described in the previous report (Asano et al, 2003). The hydrolyzed slurry was fi~Itered and the filtrate was dried.…”
Section: Methodsmentioning
confidence: 99%
“…A significantly higher level of propionate was found to be produced from MOSs compared to fructooligosaccharides and β‐1,4‐mannobiose 60 . Similar results for coffee MOSs were obtained in an in vivo rat study 61 . The addition of 5% MOSs to the diet for 28 days resulted in a proportional increase of up to 36.5 mmol/L of propionate in the cecum.…”
Section: Substrates Affecting Propionate Productionsupporting
confidence: 73%
“…60 Similar results for coffee MOSs were obtained in an in vivo rat study. 61 The addition of 5% MOSs to the diet for 28 days resulted in a proportional increase of up to 36.5 mmol/L of propionate in the cecum.…”
Section: Mannooligosaccharidesmentioning
confidence: 99%
“…Several studies have shown that intake of 1–3 g/day of MOS can increase laxation frequency (15,18–20), as well as total fecal fat content (14,21). Further, in vitro (22) and animal studies (23,24) have indicated that MOS intestinal fermentation may increase the production of short‐chain fatty acids (SCFA) which may have an impact on lipid metabolism and subsequently improve insulin sensitivity. However, effects of MOS intake on thermogenesis and beta oxidation have not been examined.…”
Section: Introductionmentioning
confidence: 99%